Factors of Decreased Visual Acuity in Primary and Junior High School Students Aged 6-15 Years in the Working Area of Cimareme Community Health Center, West Bandung Regency - Karim, Akbal Nur; Santosa, Agung (Newinera Publisher, 2023)
The issue of decreased visual acuity in children, especially in primary and junior high school ages, has not been well socialized. Many children and parents still lack understanding regarding the risk factors associated with daily activities that contribute to decreased visual acuity. This study is an analytical observational research using a cross-sectional approach. The research was conducted on all students from grade I to grade VI of SD Unggulan Al-Amin, totaling 266 individuals, and all students from grade VII to grade IX of SMP Unggulan Al-Amin, totaling 120 individuals. Data were collected through visual acuity examinations using the Snellen chart at 6 meters and interviews guided by a questionnaire. Data were analyzed using the chi-square test. Among the students of SD Unggulan Al-Amin, six factors were found to have a significant relationship with decreased visual acuity based on the chi-square test. These six factors are reading position (p=0.001), frequency of cellphone use (p=0.000), duration of gadget use (p=0.001), gadget usage position (p=0.040), distance while watching TV (p=0.046), and distance from eyes to cellphone screen (p=0.019). Among the students of SMP Unggulan Al-Amin, eight factors were found to have a significant relationship, including reading position (p=0.00), frequency of cellphone use (p=0.000), duration of gadget use (p=0.000), gadget usage position (p=0.000), frequency of TV watching (p=0.001), duration of TV watching (p=0.000), distance while watching TV (p=0.000), and distance from eyes to cellphone screen (p=0.000). Decreased visual acuity was experienced by 56.8% of students from SD Unggulan Al-Amin and 18.3% of students from SMP Unggulan Al-Amin. There is a significant relationship between risk factors and decreased visual acuity, including reading position, frequency of cellphone use, duration of gadget use, gadget usage position, frequency of TV watching, duration of TV watching, distance while watching TV, and distance from eyes to cellphone screen.